Depressive symptoms before and after antiretroviral therapy initiation among older-aged individuals in rural Uganda - Manne-Goehler, Jennifer; Bärnighausen, Till (Aids and behavior, 2019)
This study aims to characterize associations between depression symptom severity and HIV infection, both prior to and in years after ART initiation, among older adults. The Ugandan Non-Communicable Diseases & Aging Cohort Study (UGANDAC) is a study of 154 PLWH on ART and 142 community-based, HIV-negative controls. The Hopkins Checklist (HSCL), a 15-item depression scale, was used to screen for depression. We estimate differences in depressive symptoms by HIV and ART status and use multivariable log binomial regression to quantify differences in probable depression between PLWH on ART. HIV-infected and HIV-uninfected participants had a similar age (mean 52.0 vs. 51.9, p = 0.854) and sex distribution (47.4 vs. 47.9% female, p = 0.934). PLWH on ART had lower depression symptom severity than HIV-uninfected controls (mean score: 1.50 vs. 1.60, p = 0.006) and a lower prevalence of probable depression (21.4 vs. 33.8%, p = 0.017). Among 102 PLWH with pre-ART depression screening scores available, their mean depression symptom severity was similar to HIV-uninfected participants (mean 1.56 vs. 1.60, p = 0.512). In adjusted models, PLWH on ART had a lower prevalence of probable depression than HIV-negative controls [adjusted prevalence ratio: 0.68 (95% CI 0.47-0.99)]. In an observational cohort of PLWH over 40 on long-term ART and matched, community-based HIV-uninfected controls in rural Uganda, we found a lower prevalence of self-reported depression among aging PLWH on ART.